Demand Forecasting Errors - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
Demand forecasts form a key input to the economic appraisal. As such any errors present within the demand forecasts will undermine the reliability of the economic appraisal. The minimization of demand forecasting errors is therefore important in the delivery of a robust appraisal. This issue is addressed in this note by introducing the key issues, and error types present within demand forecasts (Section 1). Following that introductory section the error types are described in more detail: measurement error (Section 2), model specification error (Section 3) and External or Exogenous Errors (Section 4). The final section presents a discussion on how to manage demand forecasting errors (Section 5).